How small and authentic local brands can become global luxury niche brands: The case of four Portuguese brands - Pinho, Liliana Marisa Modesto (2019)
Small, local and authentic brands are trying to find their place in the luxury market with highly innovative products, a strong culture and high standards of craftsmanship. Even though they are successful building the substance, they are unable to conquer the status associated to a luxury brand. In this work project we explore how these brands can achieve a global niche luxury positioning through a case study research involving the analysis of four Portuguese brands. We infer recommendations to these brands and to other small, premium local brands that would benefit from “migrating” to a luxury status.